2008
DOI: 10.1029/2007ja012867
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of low‐latitude Pc1 pulsations during geomagnetic storms

Abstract: [1] We use search-coil magnetometer data from a low-latitude station in Parkfield, California (L = 1.77) to study the occurrence of Pc1 pulsations associated with geomagnetic storms. The Pc1 pulsations and storms are identified using automatic algorithms, and the statistical distributions are examined using a superposed epoch analysis technique, as a function of local time, time relative to storm main phase, and storm intensity. Results show that Pc1 pulsations are 2-3 times more likely (than normal) to be obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 31 publications
3
45
2
Order By: Relevance
“…The occurrence pattern shown in Figure 10 is typical of the patterns seen in earlier studies [ Wentworth , 1964; Engebretson et al , 2008; Bortnik et al , 2008]; few, if any, events were observed during main and early recovery phases (e.g., 14–15 April), but an increasing number occurred during the middle and late recovery phases (e.g., 16–21 April). No wave events were observed either at ST5 or at Halley during the main phase day and first recovery day of the storms that began 9 April (minimum Dst = −80), 14 April (minimum Dst = −111), or 4 May (minimum Dst = −62).…”
Section: Relation To Magnetic Stormssupporting
confidence: 76%
“…The occurrence pattern shown in Figure 10 is typical of the patterns seen in earlier studies [ Wentworth , 1964; Engebretson et al , 2008; Bortnik et al , 2008]; few, if any, events were observed during main and early recovery phases (e.g., 14–15 April), but an increasing number occurred during the middle and late recovery phases (e.g., 16–21 April). No wave events were observed either at ST5 or at Halley during the main phase day and first recovery day of the storms that began 9 April (minimum Dst = −80), 14 April (minimum Dst = −111), or 4 May (minimum Dst = −62).…”
Section: Relation To Magnetic Stormssupporting
confidence: 76%
“…With the large southward IMF B z and large AE index, the EMIC waves preferentially occur in the dusk sector with large amplitudes [ Erlandson and Ukhorskiy , ; Halford et al , ; Usanova et al , ]. Moreover, their source region is also observed to extend to lower L shells with increasing storm intensity [ Bortnik et al , ]. Lyons and Thorne [] pointed out the anomalous resonant interactions of EMIC waves with relativistic electrons, which are able to scatter the electrons into the bounce loss cone through pitch angle scattering and thus cause precipitations into the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is well-known that Pc1 pulsations are associated with enhanced geomagnetic activity (Wentworth, 1964;Heacock and Kivinen, 1972;Bortnik et al, 2008), we test the possible connection between geomagnetic activity and earthquakes directly. Shown in panel (c) is the result of a superposed epoch analysis, performed as above, but using a sequence of 220 storm sudden commencements (SSC's) as the fiducial time.…”
Section: Earthquake Probabilitymentioning
confidence: 99%
“…3c is straightforward to interpret and shows important absolute trends, it is nevertheless somewhat deficient in that it obscures how Pc1 occurrence behaves compared with its typical behavior. To address this issue, we derive the relative probability of Pc1 occurrence similar to Bortnik et al (2008). First, the entire set of identified Pc1 pulsations is binned into 12 LT bins.…”
Section: Superposed Epoch Analysismentioning
confidence: 99%
See 1 more Smart Citation